Sedentary Behavior and Musculoskeletal Discomfort Are Reduced When Office Workers Trial an Activity-Based Work Environment. Issue 9 (September 2016) - Foley, Bridget; Engelen, Lina; Gale, Joanne; Bauman, Adrian; Mackey, Martin
Abstract : Objective: The aim of this study was to evaluate the effect of an activity-based work (ABW) office environment on physical activity and sedentary behavior, work ability, and musculoskeletal discomfort. Methods: Eighty-eight office workers trialed ABW for 4 weeks. Accelerometer and self-reported outcomes were measured at baseline, end-intervention, and follow-up. Data were analyzed using linear mixed models. Results: Accelerometry measured sedentary time; sedentary breaks and step count did not significantly change from baseline to end-intervention ( P  = 0.13, 0.09, 0.18, respectively). Self-reported sitting-time was 14% lower, with standing-time and walking 11% and 3% higher in ABW than baseline ( P  < 0.01 for all). Low back pain was lower in ABW than baseline (odds ratio 2.0, 95% confidence interval 1.1 to 3.7). Work ability reduced from 8.4 to 7.8 points ( P  < 0.01) at follow-up. Conclusions: ABW environment appears to reduce self-reported sedentary behavior and low back pain and increase standing time.